Dynamics of Respiratory System Indices of Cadets of Higher Military Educational Institutions During Kettlebell Lifting Training - Lytvynenko, A.; Prontenko, K. (My University, 2020)
The influence of the kettlebell lifting training on the functional abilities of the respiratory system of the cadets during studying at higher military educational institutions (HMEI) is examined in the article. Also, a comparative analysis of the indices of the cadets’ respiratory system depending on their sports qualification in kettlebell lifting is conducted. Cadets of the 1st – 5th years of study (n=474) of S. P. Koroliov Zhytomyr Military Institute who were studying according to the current system of physical training (group А, n=416) and cadets who were attending a kettlebell lifting classes during the studying (group B, n=58) took part in the investigation. The investigation of the cadets’ respiratory system efficiency was conducted concerning these indicators: vital capacity, duration of holding of breathing during the inhalation, duration of holding of breathing during the exhalation, respiratory muscles endurance, life index and maximal oxygen consumption. Authentically better respiratory system indices in group B in comparison with group A are discovered (р < 0.05–0.001) that proves the efficiency of kettlebell lifting activity concerning the improvement of morphofunctional development of the cadets in contrast to the current system of physical training at HMEI. The respiratory system indices are improved with increased sports qualification of kettlebell lifters that confirms the positive effect of kettlebell lifting activity on the functional capacity of the main organism systems of cadets. Investigation shows the necessity of the implementation of kettlebell lifting to the physical training of the cadets who are the future Ukrainian Armed Forces’ officers in order to ensure high efficiency of the future professional activity, improve health and working capacity.
Keywords: respiratory system; kettlebell lifting; cadets